2019
DOI: 10.21037/med.2019.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Cervical mediastinoscopy and video-assisted mediastinoscopic lymphadenectomy for the staging of non-small cell lung cancer

Abstract: The staging of mediastinal lymph nodes is essential for planning the most adequate treatment for patients with non-small cell lung cancer (NSCLC). For this reason, the current American and European guidelines recommend obtaining tissue confirmation of any mediastinal abnormality seen on chest computed tomography (CT) and positron emission tomography (PET). This can be done by endoscopic techniques, such as endobronchial ultrasonographic fine-needle aspiration (EBUS-FNA), esophageal ultrasonographic FNA (EUS-FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The presence of lymph nodes whose size exceed 10 mm on the short axis should be considered a predictor of malignancy. However, results from studies focused in the accuracy of lymph node size for malignancy prediction have demonstrated that size alone is insufficient to confirm or discard metastatic infiltration of lymph nodes because of the low sensitivity (55%) reported for this technique (1)(2)(3)(4)(5)(6)(7)(8)(9)15). Additionally, the clinical relevance of nodal enlargement is limited because metastases have been found in about 20% of lymph nodes with dimensions under 1 cm on the short axis (6).…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of lymph nodes whose size exceed 10 mm on the short axis should be considered a predictor of malignancy. However, results from studies focused in the accuracy of lymph node size for malignancy prediction have demonstrated that size alone is insufficient to confirm or discard metastatic infiltration of lymph nodes because of the low sensitivity (55%) reported for this technique (1)(2)(3)(4)(5)(6)(7)(8)(9)15). Additionally, the clinical relevance of nodal enlargement is limited because metastases have been found in about 20% of lymph nodes with dimensions under 1 cm on the short axis (6).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…The correct evaluation of mediastinal and hilar lymph nodes (Ns) is critical for choosing the best option for the management and treatment of patients with non-small cell lung cancer (NSCLC) who are potential candidates for curative therapeutic strategies, including surgery, radiotherapy, chemotherapy, and multimodal treatments (1)(2)(3)(4)(5)(6)(7). For preoperative mediastinal staging the current guidelines state that it is important to confirm the absence of neoplastic mediastinal involvement with the highest level of certainty possible before performing surgical resection (1,3).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations